2019
DOI: 10.1016/j.nicl.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting conversion from clinically isolated syndrome to multiple sclerosis–An imaging-based machine learning approach

Abstract: Magnetic resonance imaging (MRI) scans play a pivotal role in the evaluation of patients presenting with a clinically isolated syndrome (CIS), as these may depict brain lesions suggestive of an inflammatory cause. We hypothesized that it is possible to predict the conversion from CIS to multiple sclerosis (MS) based on the baseline MRI scan by studying image features of these lesions. We analyzed 84 patients diagnosed with CIS from a prospective observational single center cohort. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 38 publications
0
23
0
2
Order By: Relevance
“…For support to patient counseling, prognosis, and therapy, attention has increasingly been turned to artificial intelligence, exploiting the ability of Machine learning (ML) approaches to extract complex relations among existing data without requiring a priori models linking input and output variables [18]. Different problems have been addressed, such as the classification of disease phase at the time of analysis [19][20][21] or evaluation of the probability of transition from Clinically Isolated Syndrome (CIS) to definite multiple sclerosis within 1 to 3 years [22][23][24]. Others have attempted to derive predictions on the course of individual patients or have investigated the variables that best predict disease evolution in time [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For support to patient counseling, prognosis, and therapy, attention has increasingly been turned to artificial intelligence, exploiting the ability of Machine learning (ML) approaches to extract complex relations among existing data without requiring a priori models linking input and output variables [18]. Different problems have been addressed, such as the classification of disease phase at the time of analysis [19][20][21] or evaluation of the probability of transition from Clinically Isolated Syndrome (CIS) to definite multiple sclerosis within 1 to 3 years [22][23][24]. Others have attempted to derive predictions on the course of individual patients or have investigated the variables that best predict disease evolution in time [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…In MS, the application of ML thus far has mainly been for classifying participants into the different disease stages (e.g. clinically isolated syndrome (CIS), relapsing–remitting multiple sclerosis (RRMS), and SPMS), 24 or for predicting transition from CIS to clinically definite MS, 57 and less for predicting disability progression. One study showed that an ensemble of 10 support vector machines (SVMs) outperformed logistic regression (LR) for predicting disability progression (defined by an Expanded Disability Status Scale (EDSS) increase of 1.0) within 5 years in individuals with EDSS <4.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive studies in other neurological disorders are less frequent. Zhang et al [13] predicted progression from clinically isolated syndrome to multiple sclerosis using characteristics of MRI white matter lesions with a balanced accuracy of 72%. Instead of predicting the future, one can also use ML to go back in time and estimate the date at which the disease started.…”
Section: Predicting Evolutionmentioning
confidence: 99%
“…Computer-aided diagnosis has moved from the discrimination between a single disease and controls to differential diagnosis [4*-8]. In addition to diagnosis, models for predicting the subsequent evolution of patients have been developed [9][10][11][12][13]. Most of the initial work focused on neuroimaging as the data source, because it is inherently digital and databases are easy to access.…”
Section: Introductionmentioning
confidence: 99%